A systematic review of secondhand smoke exposure in a car: Attributable changes in atmospheric and biological markers. (May 2015) - Raoof, Sana A; Agaku, Israel T; Vardavas, Constantine I
Exposure to secondhand smoke (SHS) has been linked to disease, disability, and premature death. While several countries have enacted smoke-free legislations, exposure to SHS may still occur in unregulated private environments, such as in the family car. We performed a systematic review of peer-reviewed literature in PubMed and Web of Science up to May 2013. Articles were selected if they provided a quantitative measure of SHS exposure (biological or atmospheric markers); the study was conducted inside a car; and the assessed exposure was attributable to cigarette combustion. From 202 articles identified, 12 met the inclusion criteria. Among all studies that assessed smoking in cars with at least one window partially open, the particulate matter 2.5 μm or less in diameter (PM2.5 ) concentrations ranged from 47 μg/m 3 to 12, 150 μg/m 3 . For studies with all windows closed, PM2.5 ranged from 203.6 μg/m 3 to 13, 150 μg/m 3 . SHS concentration in a car was mediated by air-conditioning status, extent of airflow, and driving speed. Smoking in cars leads to extremely high exposure to SHS and increased concentration of atmospheric markers of exposure—even in the presence of air-conditioning or increased airflow from open windows. This clearly shows that the only way to protect nonsmokers, especially children, from SHS within cars is by eliminating tobacco smoking.